2020
DOI: 10.1111/1440-1681.13278
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox B5 suppression attenuates proliferation and elevates apoptosis in hepatoma cell lines through ERK/MDM2 signalling

Abstract: Homeobox B5 (HOXB5), a member of the HOX gene family, is an important gene in tumourigenesis. However, its role in hepatocellular carcinoma (HCC) cell proliferation and apoptosis remains unclear. In this study, we investigated the role and regulation mechanism of HOXB5 in HCC cell lines Hep3B and LM6. The data indicated high expression of HOXB5 in HCC tissues and cell lines. In HCC cells, inhibition of HOXB5 by transfection with HOXB5 siRNA significantly constrained cell viability, and Bcl‐2 levels, and it inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…In the present study, we found that HOXB5 is markedly upregulated in HCC tissues compared to paired-adjacent noncancerous controls, which was consistent with other research groups ( 17 , 18 ). In addition, we demonstrated that overexpression of HOXB5 was associated with tumor size, tumor-nodule metastasis, TNM stage, and relatively unfavorable OS and DFS.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that HOXB5 is markedly upregulated in HCC tissues compared to paired-adjacent noncancerous controls, which was consistent with other research groups ( 17 , 18 ). In addition, we demonstrated that overexpression of HOXB5 was associated with tumor size, tumor-nodule metastasis, TNM stage, and relatively unfavorable OS and DFS.…”
Section: Discussionsupporting
confidence: 93%
“…Our data further showed that HOXB5 enhanced survival by suppression of proapoptotic gene BCL2L11. This observation is supported by experiments performed in hepatoma cell lines [32]. Interestingly, BCL2L11 is reportedly repressed by miR10a in neurons associated with Parkinson's disease and by miR17 in B-cell development [33,34], highlighting a role for these genes in SC-1 and more generally in B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 73%
“…Further, gene translocation at t (11;12) (p15;q13) generated a NUP98/ HOXC13 fusion protein. The study showed that the fusion that occurred between the 16th exon of the Hou et al 2012;Mohankumar et al 2007;Wang et al 2015;Yuan et al 2016 HOXA10 chr7:27,170,605-27,174,320 Bladder cancer, colorectal cancer, acute myeloid leukemia, laryngeal squamous cell cancer, pancreatic cancer Cui et al 2014;Guo et al 2020;Li et al 2020a;Liu et al 2019a;Yuan et al 2018 HOXA13 chr7:27,194,364-27,200 Gao et al 2020;Hong et al 2015;Lee et al 2015;Lee et al 2020;Su et al 2020;Xu et al 2018;Zhang et al 2018 HOXB7 chr17:48,607,232-48,611,017 Esophageal squamous cell carcinoma, gastric cancer, glioma, cutaneous squamous cell carcinoma, breast cancer, pancreatic cancer, hepatocellular carcinoma, acute lymphoblastic leukemia, multiple myeloma, lung adenocarcinoma, colorectal cancer Gao and Chen 2018;He et al 2017;Huo et al 2019;Liao et al 2011;…”
Section: Genetic Regulation Of Hox Genes In Cancermentioning
confidence: 99%
“…In HCC, overexpressed HOXB5 inhibits apoptosis by increasing the protein levels of BCL-2 and decreasing the pro-apoptotic proteins Cyt c, BAX, and caspase-3. Further, it was demonstrated that HOXB5 could induce the expression of murine double minute 2 oncogene ( MDM2 ) in hepatoma cells through ERK/MDM2 signaling (Su et al 2020 ). In CC, elevated HOXC6 functions as a positive regulator of anti-apoptosis.…”
Section: Role Of Hox-targeted Signaling In Metastatic Progressionmentioning
confidence: 99%